Effects of ovariectomy on inputs from the medial preoptic area to the ventromedial nucleus of the hypothalamus of young adult rats - Pereira, Lais da Silva; Gobbo, Denise Ribeiro; Ferreira, Jozelia Gomes Pacheco; Horta-Junior, Jose de Anchieta de Castro e [UNESP]; Sa, Susana Isabel; Bittencourt, Jackson Cioni (Wiley-Blackwell, 2020)
Puberty is an important phase of development when the neural circuit organization is transformed by sexual hormones, inducing sexual dimorphism in adult behavioural responses. The principal brain area responsible for the control of the receptive component of female sexual behaviour is the ventrolateral division of the ventromedial nucleus of the hypothalamus (VMHvl), which is known for its dependency on ovarian hormones. Inputs to the VMHvl originating from the medial preoptic nucleus (MPN) are responsible for conveying essential information that will trigger such behaviour. Here, we investigated the pattern of the projection of the MPN to the VMHvl in rats ovariectomized at the onset of puberty. Sprague Dawley rats were ovariectomized (OVX) at puberty and then subjected to iontophoretic injections of the neuronal anterograde tracerPhaseolus vulgaris leucoagglutinininto the MPN once they reached 90 days of age. This study analysed the connectivity pattern established between the MPN and the VMH that is involved in the neuronal circuit responsible for female sexual behaviour in control and OVX rats. The data show the changes in the organization of the connections observed in the OVX adult rats that displayed a reduced axonal length for the MPN fibres reaching the VMHvl, suggesting that peripubertal ovarian hormones are relevant to the organization of MPN connections with structures involved in the promotion of female sexual behaviour.
Keywords: female sexual behaviour; neural circuitry; Phaseolus vulgarisleucoagglutinin; puberty; steroids; three-dimensional reconstruction